Comparison of a Clinic-Based ELISA Test Kit with the Immunofluorescence Antibody Test for Assaying Leishmania infantum Antibodies in Dogs. (26th September 2013) - Proverbio, Daniela; Spada, Eva; Baggiani, Luciana; Bagnagatti De Giorgi, Giada; Perego, Roberta
Abstract : This study compares a rapid Immunospecific Kalazar Canine Rapid Spot IF with the gold standard test (indirect fluorescent antibody test (IFAT)) for detection of Leishmania infantum specific IgG serum antibodies in naturally exposed dogs. Serum samples were obtained from 89 healthy dogs and dogs affected by canine leishmaniosis (CanL). IgG-IFAT titers ≥80 were considered positive. Anti- L. infantum IgG antibodies were found in 54 samples with titers ranging from 1 : 80 to 1 : 5120. The performance of the rapid Immunospecific Kalazar was evaluated using a ROC curve. The area under the ROC curve of 0.957 was significantly different from 0.5 (P < 0.0001 ), and therefore it can be concluded that the rapid Immunospecific Kalazar has the ability to distinguish canine sera with and without L. infantum IgG. The best performance of the test was at a cutoff >0 (sensitivity 92.6%, specificity 97%). The test can be used for disease screening if the cutoff is >0 (highest sensitivity, 92.6%) and is recommended as confirmatory test for the presence of L. infantum IgG antibodies if the cutoff is set >2 (highest specificity, 100%).